PARENTAL ENGAGEMENT DALAM PIAUD: ANTARA IDEALITAS DAN REALITAS PENDAMPINGAN BELAJAR ANAK USIA DINI - Susilawati; Afandi, Nur Kholik (MAANA: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Abstract This study examines parental engagement in Pendidikan Islam Anak Usia Dini (PIAUD) by analyzing the gap between ideal conditions and actual practices in early childhood learning assistance. The study aims to explore parental involvement and formulate a contextual, value based approach. A qualitative descriptive method was employed through semi-structured interviews and observations involving parents and teachers. The findings reveal that although parents are aware of their important role and actively participate in children’s learning, their involvement tends to focus more on cognitive aspects rather than holistic development, including spiritual and character building. Several constraints were identified, such as limited time, lack of pedagogical understanding, emotional challenges, and weak communication with schools. This gap occurs because parental engagement has not yet been supported by practical, structured, and contextually relevant models. The study concludes that strengthening collaboration between parents and schools, along with integrating Islamic values into daily learning activities, can enhance the quality of children’s development. This research contributes by emphasizing the need for a holistic and applicable parental engagement model in PIAUD contexts.